Understanding Learning Difficulty Issues Based on Psychology in Primary School Age Students - Rohma, Wulidatul; mu'alimin, mu'alimin; Usriyah, Lailatul; sutomo, moh (Attadib: Journal of Elementary Education, 2024)
AbstractLearning difficulties are a problem that can arise anywhere and can be experienced by anyone. Learning difficulties are not always caused by low intelligence, but can also be caused by non-intelligence factors. Parenting has a role in children's development, including their personality and also in their learning process. This research was conducted to find out the causes of learning difficulties experienced by school-age children. The method used is qualitative research, with an explanatory case study. The subject in this study is a 10-year-old school-age child. The data collected in this research is by using interview, observation, intelligence test (CFIT test), and graphic test. The results showed that the learning difficulties experienced by the subject were not only caused by intelligence factors, but also influenced by the parenting received by the subject in the family. The subject has an intelligence level below average, which puts him in the category of slow learners. In addition, permissive parenting and excessive attention from family members, especially the grandmother, also contributed to the subject's learning difficulties.Keyword; Learning Difficulty Issues, Psychology, Primary School Age AbstrakKesulitan belajar merupakan masalah yang dapat muncul di mana saja dan dapat dialami oleh siapa saja. Kesulitan belajar tidak selalu disebabkan oleh faktor intelegensi yang rendah, tetapi juga dapat disebabkan oleh faktor non-intelegensi. Pola asuh orang tua memiliki andil dalam perkembangan anak, termasuk kepribadiannya dan juga dalam proses belajarnya. Penelitian ini dilakukan untuk mengetahui penyebab kesulitan belajar yang dialami anak usia sekolah. Metode yang digunakan adalah penelitian kualitatif, dengan studi kasus eksplanatoris. Subjek dalam penelitian ini adalah seorang anak usia sekolah yang berusia 10 tahun. Data yang dikumpulkan dalam penelitian ini adalah dengan menggunakan metode wawancara, observasi, tes inteligensi (tes CFIT), dan tes grafis. Hasil penelitian menunjukkan bahwa kesulitan belajar yang dialami oleh subjek selain disebabkan oleh faktor inteligensi, juga dipengaruhi oleh pola asuh yang diterima oleh subjek dalam keluarga. Subjek memiliki tingkat intelegensi di bawah rata-rata, yang menempatkannya dalam kategori anak lambat belajar (slow learner). Selain itu, pola asuh yang permisif dan perhatian yang berlebih dari anggota keluarga, khususnya nenek, juga berkontribusi pada kesulitan belajar yang dialami subjek.Kata kunci: Masalah Kesulitan Belajar, Psikologi, Usia Sekolah Dasar